2018
DOI: 10.18203/2349-3291.ijcp20181538
|View full text |Cite
|
Sign up to set email alerts
|

A study on status of neonatal transport to a level III neonatal intensive care unit

Abstract: In most of these new-born babies, the ineffective transport system results in hypoglycemia, hypothermia, cyanosis and other complications. These complications further increase the mortality among these sick neonates. ABSTRACT Background:In the past decade, great advancements in Neonatal care contributed to a fall in IMR. A further fall in IMR can only be achieved by improving the neonatal transport facilities. Hence to assess the current status of neonatal transport we undertook this study. Methods: This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Research by Sampathkumar et al found causes of referral to be preterm 41%, birth asphyxia 27% and RDS 21%. 13 RDS was at 35.9% in the study by Jajoo et al 14 Research by Kumar et al found 32.6% referred for birth asphyxia with HIE; and 13.4% for prematurity with LBW. 15 In the study by Shalini et al 50% were referred for LBW/preterm, 22% for meconium aspiration and 15% for birth asphyxia.…”
Section: Discussionmentioning
confidence: 90%
“…Research by Sampathkumar et al found causes of referral to be preterm 41%, birth asphyxia 27% and RDS 21%. 13 RDS was at 35.9% in the study by Jajoo et al 14 Research by Kumar et al found 32.6% referred for birth asphyxia with HIE; and 13.4% for prematurity with LBW. 15 In the study by Shalini et al 50% were referred for LBW/preterm, 22% for meconium aspiration and 15% for birth asphyxia.…”
Section: Discussionmentioning
confidence: 90%
“…Hence the increased risk of vehicle breakdown. In other developing countries such as India, Sampathkumar et al (36) stated that in resource-poor settings, most of the available ambulances are not sufficiently equipped to handle critically ill neonates.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…There is enough evidence to support that transport by a skilled organized team reduces neonatal morbidity and mortality [ 9 , 13 , 14 ]. The goal of all neonatal transport teams should be transporting a well-stabilized neonate.…”
Section: Introductionmentioning
confidence: 99%